Self-destructive behaviors and type II Diabetes Mellitus: possible triggers for non-adherence to treatment - dos Santos, Stefani Gabriela da Silva; Guazina, Félix Miguel Nascimento (Disciplinarum Scientia | Saúde, 2023)
In Brazil, there are about 13 million people living with diabetes mellitus (DM), when poorly controlled, can generate several complications, such as peripheral neuropathy and even amputation of limbs. Most cases of leg or foot amputation are a consequence of lack of preventive self-care. Self-care is an act of self-preservation, however, there are behaviors incoherent with this search, the so-called self-destructive behaviors. This study aims to identify the possible triggers of self-destructive behaviors in patients diagnosed with type 2 diabetes mellitus (DM2) with peripheral neuropathy. This is a qualitative study, exploratory and interpretative in nature, with a descriptive character. A semi-structured interview was used as an instrument with eight patients with peripheral neuropathy due to DM. The data were analyzed from content analysis and categorized. Three categories were added that can influence self-destructive behaviors: a) the conception of health and disease: the need to look beyond the disease; b) DM2 and its invisibility; and c) the psychological dimension of DM care. From the interviews and theoretical contribution, this study sought to reflect on the possible crossings regarding the treatment of DM2.